KOLABORASI MASYARAKAT SIPIL, POLITIK DAN EKONOMI DALAM PEMANFAATAN MODAL SOSIAL (KASUS PELESTARIAN LINGKUNGAN PESISIR PADA MASYARAKAT BALI AGA- DESA LES BALI UTARA) - Mudana, I Wayan (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract This research aims to understand the back ground the collaboration of civil community, politic and economic in presenting social capital, shape of ideal text and social capital text that is presented and process social process, and so controlling of sociality that’s carried out in guiding to the beach environment conservation at Les Bali Age, North Bali. This research using qualitative approach, informant is determined by snowball purposive system, collecting data is done with interviewing, observation, document method, while data analyze is carried out through triangulation, which is going on with interpretation process. According to that problem is known that collaboration of civil community, politic and economic to present the social capital in beach circles collaboration at Les village community is based on awareness to environment and its resources that has the value to civil community, economic and politic. In that framework some kind of social capital that belongs to local community in the system of cultural value, institution, activity pattern and physical culture have been used in optimal manner. The shape of ideal text and social text of social capital that’s presented by civil community, economic and politic, there is Tri Hita Karana ideology, Nyegara gunung ideology, development which has environment perception, with clear beach and still in eternal condition, awig-awig agreement, family group/dadia, fisherman group, pecalang segara (sea guider), Pokmaswas, strengthen the similarity, help each others and also believe each others among community members, while the physical culture that’s developed are; beach support, technology development of ridge of rock, technology development of fish catching that’s clever around environment. Investment of social capital is started by socialization process, the strength of social trust to the idea of beach circles eternity, by involving the LSM, village apparatus, figure of local community, and continued with developing the fisherman group, who’s catching the goldfish and circles eternity, pecalang and making the regulation. The social control mechanism that’s carried out, has their characteristic from high level and low level, sekala and niskala character, started by socialism process that’s continued by LSM, water police, Pokmaswas, village apparatus, pecalang, and locan fisherman group
Keywords: Key words: collaboration, social capital, environment conservation.